Synthesis of biofunctionalized silica nanospheres to separate GST-tagged proteins. Issue 6 (June 2016) - Zou, Xueyan; Li, Liangliang; Lu, Haitao; Zhang, Yutao; Zhao, Yanbao; Zhang, Yu; Guo, Quanhui
Graphical abstract: Highlights: Hollow silica nanospheres (NSs) with Glutatione group (SiO2 -GSH) have been prepared. SiO2 -GSH NSs were applied to purify GST-tagged proteins without any preprocessing. The capacity of separated protein barely changed after three times reuse. The detection limit is lower than 1.0 × 10 −6  mol/L to the target proteins. The separated capacity of the SiO2 -GSH NSs is as much as 89.9 μmol/g. Abstract: A Thiol-functionalized silica hollow nanospheres(denoted as SiO2 -SH NSs) were prepared through a hydrothermal route. The SiO2 -SH NSs were conjugated with glutathione group (denoted asGSH) to afford SiO2 -GSH NSs. The as-prepared SiO2 -GSH sample has hollow structure and exhibits an average diameter of about 45 nm and a wall thickness of 10 nm. The SiO2 -GSH NSs were used to separate three kinds of GST-tagged proteins (GST-tagged GPX, GST-tagged LOV and GST-tagged 210-6P). These SiO2 -GSH NSs exhibit negligible non-specific adsorption, high binding capacity (89.9 μmol/g), the low detection limit (1.0 × 10 −6  mol/L) and reuse property, showing great potentiality in purifying GST-tagged proteins.